DEFAULT IN MUSYARAKAH CONTRACT A CRITICAL EXAMINATION OF LEGAL CERTAINTY IN ISLAMIC ECONOMICS: indonesia - Nurrahmawaty, Nurrahmawaty (Universitas Muhammadiyah Surabaya, 2025)
The musyarakah (partnership) contract is a key component in Islamic finance, enabling joint economic ventures. However, wanprestasi (breach of contract) threatens its stability, undermining trust and hindering the sector’s growth. This study explores the forms and impacts of wanprestasi in musyarakah contracts and its implications for legal certainty in Islamic economics. Using a qualitative, literature-based approach, it examines Islamic legal principles and contemporary practices in Islamic finance. Findings show that wanprestasi can involve financial breaches (e.g., failure to contribute capital), managerial issues (e.g., mismanagement, lack of transparency), and violations of Sharia. To address these challenges, the study proposes a comprehensive approach grounded in Islamic values, emphasizing justice, honesty, and good faith; utilizing religious courts and Sharia arbitration; applying appropriate guarantees; and promoting restorative justice. It also highlights the role of Islamic financial institutions in risk management and education. By reinforcing these measures, the legal certainty and trust in musyarakah contracts can be strengthened. Related studies support these findings, emphasizing the need for Sharia adherence and clear rights allocation in Islamic finance.